Direct and First Order Derivative Spectrophotometric Determination of Cobalt(II) using Diacetylmonoxime isonicotinoyl hydrazone - Devanna, N.; Jayaveera, K.N.; Chandra Sekhar, K.B. (Asian Journal of Chemistry, 2016)
Diacetylmonoxime isonicotinoyl hydrazone (DMIH) used as chromogen for cobalt(II)·DMIH reagent gives bright yellow coloured water-soluble complex in acidic buffer medium. The maximum absorbance is observed in the pH range 6–7. The molar absorptivity and Sandell’s sensitivity of Co(II) at λmax 334 was found to be 1.25 × 104 L mol–1 cm–1 and 0.0047 μg/cm2. Beer’s law validity range 0.235–2.35 μg/mL. Cobalt forms 1 : 1 complex with DMIH and stability constant of the complex was 1.75 × 105. First order derivative technique has been developed. The derivative amplitude was measured by the peak zone method and shows maximum amplitude at 360 nm in basic buffer medium. The developed first order derivative spectrophotometric method was used for the determination of cobalt(II) in alloy samples.